Regulation of cellular proliferation and intimal formation following balloon injury in atherosclerotic rabbit arteries. - Simari, R D (1996)
Injury to atherosclerotic arteries induces the expression of growth regulatory genes that stimulate cellular proliferation and intimal formation. Intimal expansion has been reduced in vivo in nonatherosclerotic balloon-injured arteries by transfer of genes that inhibit cell proliferation. It is not known, however, whether vascular cell proliferation can be inhibited after injury in more extensively diseased atherosclerotic arteries. Accordingly, the purpose of this study was to investigate whether expression of recombinant genes in atherosclerotic arteries after balloon injury could inhibit intimal cell proliferation. To test this hypothesis, we examined the response to balloon injury in atherosclerotic rabbit arteries after gene transfer of herpesvirus thymidine kinase gene (tk) and administration of ganciclovir. Smooth muscle cells from hyperlipidemic rabbit arteries infected with adenoviral vectors encoding tk were sensitive to ganciclovir, and bystander killing was observed in vitro. In atherosclerotic arteries, a human placental alkaline phosphatase reporter gene was expressed in intimal and medial smooth muscle cells and macrophages, identifying these cells as targets for gene transfer. Expression of tk in balloon-injured hyperlipidemic rabbit arteries followed by ganciclovir treatment resulted in a 64% reduction in intimal cell proliferation 7 d after gene transfer (P = 0.004), and a 35-49% reduction in internal area 21 d after gene transfer, compared with five different control groups (P < 0.05). Replication of smooth muscle cells and macrophages was inhibited by tk expression and ganciclovir treatment. These findings indicate that transfer of a gene that inhibits cellular proliferation limits the intimal area in balloon-injured atherosclerotic arteries. Molecular approaches to the inhibition of cell proliferation in atherosclerotic arteries constitute a possible treatment for vascular proliferative diseases.